Examining the relationship between chronic kidney disease, dyslipidaemia, and dysglycemia: a prospective study - Ghosh, Anirban; Dutta, Anirban; Kayet, Arpita (International Journal of Research in Medical Sciences, 2024)
Background: Chronic kidney disease (CKD) results in profound lipid disorders, which stem largely from dysregulation of high-density lipoproteins (HDL) and triglyceride-rich lipoprotein metabolism. Objectives were to evaluate the correlation between chronic kidney disease, dyslipidaemia and dysglycemia. Methods: In-patient and outpatient department (OPD) of department of medicine, COM and JNM Hospital, Kalyani. Cases are defined as patients (>20 years of age) with a diagnosis of CKD (non-oedematous). The controls are defined as age and gender-matched patients (>20 years) attending medicine OPD/indoor without diagnosis of CKD. Results: Among the CKD cases, 30 individuals were diagnosed as overtly diabetic, whereas in the control group, 22 participants had fasting blood sugar (FBS) levels equal to or exceeding 126 mg/dl. The mean FBS was 111 mg/dl (standard deviation (SD) 44 mg/dl) in the CKD group and 91 mg/dl (SD 31 mg/dl) in the control group. The difference in FBS levels between the CKD patients’ group and the control group was statistically significant (p value=0.001). Conclusions: Hyperglycaemia is also significantly associated with CKD in form of increased fasting blood sugar (47% among cases as compared to 30% in control) and increased post-prandial blood sugar (49% in cases as compared to 36% in controls). Dyslipidaemia occurs in CKD cases (39% among CKD cases and in 24% of controls) in the form of increased triglycerides (TG), LDL and low HDL.